Life criticism and De Quincey's ethical concern over the aestheticiability of murder - Duan, Yingjie; Tian, Junwu (Orbis litterarum, 2025)
The self‐reflexive tendency in De Quincey's seemingly Kantian aestheticization of murder allows some leeway in deciphering his underlying ethical concerns. As “On the knocking at the gate in Macbeth” shows, De Quincey engages in a special kind of life writing that can be termed “life criticism,” which is not naively referential but revelatory, translating the autobiographical records of memories, experiences, and emotions into mediatory possibilities for argumentative assessments of literary and aesthetic questions. James Wood's critiques function as a compelling touchstone of De Quincey's life criticism, exhibiting how self‐referential episodes, as both the starting and end points for literary criticism, can be incorporated into serious and illuminating theoretical interrogations. Through the new prism of De Quincey's habitual mode of life criticism, his aesthetics of murder can be interpreted as a meta‐reflection upon his literary experiences with Westmorland Gazette and Blackwood's Magazine. His awareness of the facile aestheticiability of murder in the periodical press has an obvious moral implication: it shows his self‐reflexive concern over the commercialized public taste that makes him torn between insisting upon classical highbrow culture and contributing sensational magazine reading matter.